A facile electrochemical synthesis strategy for Cu2O (cubes, sheets and flowers) microstructured materials for sensitive detection of 4-nitrophenol. Issue 30 (20th July 2016) - Veeramani, Vediyappan; Sivakumar, Mani; Chen, Shen-Ming; Madhu, Rajesh; Dai, Zi-Chi; Miyamoto, Nobuyoshi
Abstract : We report a facile electrochemical synthesis strategy for Cu2 O microstructured materials deposited on a glassy carbon electrode surface as a sensor for the electrochemical detection of toxic 4-nitrophenol. Abstract : Herein, we report a facile electrochemical synthesis strategy for Cu2 O (cubes, sheets and flowers) microstructured materials deposited on a glassy carbon electrode (GCE) surface as a sensor for the electrochemical detection of toxic 4-nitrophenol (4-NP). The prepared films are characterized by using a variety of techniques, such as SEM, EDX, XRD and XPS. Notably, the proposed sensor exhibits excellent analytical parameters, such as wide linear range, high sensitivity with good detection limit, with values of 0.006–2.72 mM, 197.7 μA mM −1 cm −2 and 0.5 μM, respectively. These results reveal that the Cu2 O-modified GCE is suitable for the detection of 4-NP owing to its low cost and simple electrode preparation process. Furthermore, the modified electrode was successfully applied for the detection of 4-NP in various water samples with acceptable results and could act as a practical platform in several industrial practical applications.